An RNA-based study of the distribution of ammonia-oxidizing microorganisms in vertical sediment - Tong-tong Liu (Elsevier, 2021)
Ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) play crucial roles in ammonia nitrogen degradation in freshwater lake sediment. However, studies on ammonia-oxidizing microorganisms (AOM) in vertical sediment are still limited, especially with respect to the quantitative analysis of the vertical distribution of active AOM at the RNA level. Herein, by researching the AOM in a 75 cm vertical sediment from Lake Taihu, we found that although the total abundance of AOB throughout the whole vertical sediment surpassed that of AOA, active AOA had a closer correlation with the potential nitrification rate than active AOB. The active transcription abundance of AOM generally decreased with increasing depth, especially for AOA, while that of AOB decreased slightly. Compared to active transcription, the total abundance of AOM varied little. The community structures of AOA and AOB changed significantly with increasing depth, and Group I.1a and Nitrosomonas were the predominant clusters, respectively. Ultimately, our study demonstrated that research methods based on the RNA level can accurately reflect the vertical variation in AOM.